Turkey on a Path Towards a Changing Europe: Array - Iftode, Florin (Acta Universitatis Danubius. Relationes Internationales, 2020)
The aim of this paper is to highlight some aspects of contemporary phenomena that are developing at the gates of Europe. The migration of peoples, which could be only the beginning, surprised the administration of the European Union that proved its amateurism in the face of such small challenge. It is well known that Islamic influence in Europe is not new. Anyone who is minimally informed recognizes the role of Arab scholars in transmitting to modern Europe the teachings of ancient Greece, which - together with the inheritance of ancient Jerusalem and Rome - is part of the constituent triangle of Europe. In the current context Turkey is seeking accession to the European Union, stressing that its membership would benefit both the EU and Turkey. It actively contributes to efforts to address many challenges that affect Europe as well. As an active NATO member, Turkey has made an essential contribution to the North Atlantic alliance and to the Alliance's essential premise, namely “one for all, for all”. With all the political and military events, it has gone through, Turkey will define itself as a model for other Muslim states, showing that democracy and Islam are compatible, while promoting multiculturalism in Europe as a principle of European foreign policy becomes a necessity to deal with. global challenges. In conclusion, Turkey has a considerable distance towards the EU and obtaining the status of member state within this structure is projected as a multi-valence premisis.